2002
DOI: 10.1080/03093640208726620
|View full text |Cite
|
Sign up to set email alerts
|

%VO2max as an indicator of prosthetic rehabilitation outcome after dysvascular amputation

Abstract: In this study, independent ambulation of at least 100 metres with/without a cane was regarded as successful prosthetic rehabilitation. The subjects were classified into two groups according to this criterion at the time of discharge. The successful group attained this performance, the other group failed to reach this level. The successful group included 8 unilateral trans-femoral amputees aged 72.2 +/- 2.1 years who underwent amputation at more than 70 years, and succeeded in walking with a prosthesis. The gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 9 publications
0
45
0
2
Order By: Relevance
“…This commonly implies slower and less efficient walking in subjects with amputation than in healthy subjects (HSs) [3][4]. Thus, walking speed (WS) and oxygen consumption have been widely used as indicators of gait ability and to assess rehabilitation outcomes or prosthetic components [5][6][7][8]. Conversely, little attention has been given to upright gait stability in the population with amputation [1,4,9] and even less to gait harmony.…”
Section: Introductionmentioning
confidence: 99%
“…This commonly implies slower and less efficient walking in subjects with amputation than in healthy subjects (HSs) [3][4]. Thus, walking speed (WS) and oxygen consumption have been widely used as indicators of gait ability and to assess rehabilitation outcomes or prosthetic components [5][6][7][8]. Conversely, little attention has been given to upright gait stability in the population with amputation [1,4,9] and even less to gait harmony.…”
Section: Introductionmentioning
confidence: 99%
“…29 We previously reported that 50~60% VO 2max can be regarded as a guideline for the physical fitness level required for successful prosthetic rehabilitation in older lower limb amputees. 20,25 However our previous research did not identify the specific value of physical fitness. By choosing an optimal cut-off value of 53.9%, sensitivity was calculated as 79%, and specificity, 92%.…”
Section: Resultsmentioning
confidence: 89%
“…No significant difference was observed between the two groups in age, sex and the level of amputation. 17,20,24 and physical fitness 20,25 as important factors related to successful prosthetic rehabilitation. Our results were in agreement with previous reports in many respects.…”
Section: Resultsmentioning
confidence: 99%
“…The %VO 2 max value for the five who continued to use their prostheses after discharge ranged from 55.8 to 72.0. We have previously reported that %VO 2 max value of 50 to 60 is a valid guideline for the physical fitness required for elderly transfemoral amputees to walk independently [15][16]. Of the elderly transfemoral amputees with %VO 2 max values more than 50, 93.7 percent (30/32) were able to walk independently [16].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, besides our previous research, no other research specified the level of fitness needed for walking with a prosthesis. Our previous research demonstrated that the maximum oxygen uptake during exercise as a proportion of predicted maximum oxygen uptake (%VO 2 max) value of 50 to 60 is a valid level of fitness required for an older transfemoral patient to walk with a prosthesis [15][16].…”
Section: Introductionmentioning
confidence: 99%